Helicobacter pylori: A Paradigm Pathogen for Subverting Host Cell Signal Transmission - Naumann, Michael; Sokolova, Olga; Tegtmeyer, Nicole; Backert, Steffen (Trends in Microbiology, 2017)
Helicobacter pylori colonizes the gastric mucosa in the human stomach and represents a major risk factor for peptic ulcer disease and gastric cancer. Here, we summarize our current knowledge of the complex impact of H. pylori on manipulating host signalling networks, that is, by the cag pathogenicity island (cagPAI)-encoded type IV secretion system (T4SS). We show that H. pylori infections reflect a paradigm for interspecies contact-dependent molecular communication, which includes the disruption of cell–cell junctions and cytoskeletal rearrangements, as well as proinflammatory, cell cycle-related, proliferative, antiapoptotic, and DNA damage responses. The contribution of these altered signalling cascades to disease outcome is discussed.
Created from Fastlane, Scopus look-up
Keywords: gastric cancer; inflammation; pathogen; signalling pathways; T4SS